2019
DOI: 10.1002/jgc4.1101
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of clinical genetic healthcare professionals to provide genomic medicine: An Australian census

Abstract: We aimed to determine capacity and readiness of Australian clinical genetic healthcare professionals to provide genomic medicine. An online survey was administered to individuals with genetic counseling or clinical genetics qualifications in Australia. Data collected included: education, certification, continuing professional development (CPD), employment, and genetic versus genomic clinical practice. Of the estimated 630 clinical genetic healthcare professionals in Australia, 354 completed the survey (56.2% r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 22 publications
(32 reference statements)
0
42
0
Order By: Relevance
“…Exclusion criteria were: • Medical geneticists-we have conducted a separate study of genetic health professionals' workforce readiness (Nisselle et al, 2019a); • General practitioners (GPs)-excluded due to the differences in practice between primary, secondary and tertiary care. We have undertaken a separate study with GPs to understand their current practice of genomic medicine, including their experience with direct-to-consumer/personal genomic testing (manuscript in preparation).…”
Section: Non-genetic Medical Specialistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria were: • Medical geneticists-we have conducted a separate study of genetic health professionals' workforce readiness (Nisselle et al, 2019a); • General practitioners (GPs)-excluded due to the differences in practice between primary, secondary and tertiary care. We have undertaken a separate study with GPs to understand their current practice of genomic medicine, including their experience with direct-to-consumer/personal genomic testing (manuscript in preparation).…”
Section: Non-genetic Medical Specialistsmentioning
confidence: 99%
“…The purpose of this article is to describe in detail the methodology for developing this robust survey. Survey development was informed by literature (Chen and Kim, 2014;Gray et al, 2014;Chow-White et al, 2017;Carroll et al, 2019;Nisselle et al, 2019a;Stark et al, 2019b), theory and qualitative data, has had input from experts for content validity and was reviewed by non-genetic medical specialists representing target respondents for usability and functionality.…”
Section: Introductionmentioning
confidence: 99%
“…The term "medical specialists" is used in this study to mean "doctors specialized in a field other than general/family practice or clinical/medical genetics" (Crellin et al, 2019, pg 1-2). We have separate studies ( Figure 1) underway or completed with clinical (or medical) geneticists (Nisselle et al, 2019a) and general practitioners (GPs) as we anticipated that the needs of those who are specialized in genetics or those in primary care (i.e. GPs) may be quite distinct and therefore require separate consideration.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, our research program has three work streams around education and clinical practice: mapping the current landscape; identifying needs and future preferences; and ensuring effective education through evaluation. The present study is shown in grey and has only included medical specialists, defined as "doctors specialized in a field other than general/ family practice or clinical/medical genetics" (Crellin et al, 2019, pg 1-2 (Janinski et al, 2018); h (Nisselle et al, 2019a); i First meeting held August 2018, Sydney; j (Stark et al, 2019b). Participants groups represented in the studies within this program of research are: medical specialists (3,(9)(10)(11)(12)(13)(14)(15)(16), genetic counselors (4, 11-15), clinical geneticists (2,4,(11)(12)(13)(14)(15), bioinformaticians and medical scientists (11-15), genomic education providers (2, 12-15), general practitioners (5,6,(12)(13)(14)(15), patients or parents of patients (7, 15), system influencers and policy makers (8), oncologists (10), community practitioners (pharmacists, nutritionists, private practice genetic counselors (6).…”
Section: Introductionmentioning
confidence: 99%
“…19 The Genomics Workforce and Education program (Program 4) provides evidence to inform the education and training of those whose professional roles will be impacted by clinical genomics. Broadly, this program is mapping the current landscape of education delivery in genomics, identifying the genomic education needs and preferences of genetic and non-genetic health professionals, [20][21][22] and developing tools to support the development and evaluation of effective education programs. A combination of qualitative and quantitative methods are examining perspectives of a wide range of stakeholders, including health professionals, educators, patients, the community, scientists, and policy makers.…”
Section: Australian Genomics Programsmentioning
confidence: 99%